Updated readings of the "Little Prince" of Saint-Exupéry in year 6 and 7 at french primary schooln - Bedoin, Evelyne (Ondina - Ondine, 2020)
Based on the example of Antoine de Saint-Exupéry’s Little Prince, this article questions the updated reading of students in French primary school. On one hand, built on the features of actualizing reading defined by Yves Citton. On the other hand, buit on writings in the first person issued from the character’s diary promoted by Véronique Larrivé in her work on fictional empathy. The analysis focuses on showing how updated readings of students enter into dialogue with the text in a singular genericity. The study of some writings will highlight the modalities of this dialogue in the form of connotative accommodations. Particular attention will be paid to the use that girls and boys make, in their modes of accommodation, of gender stereotypes. Key words : update, genericity, gender, tale, fictional empathy.